Analisis Perubahan Penggunaan Lahan Di Hulu, Tengah, Dan Hilir DAS Batang Anai - prabowo, aris; Ahyuni, Ahyuni (JURNAL BUANA, 2026)
Changes in land use that occur affect the reduction of water catchment areas in the future. This study aims to determine: land-use changes in the Batang Anai watershed in the upstream, middle, and downstream areas in 2010, 2015 and 2020. The method applied in this research is a quantitative method with a descriptive approach. The results showed that changes in land use in the upstream area of the Batang Anai watershed were primary forest into rice fields covering an area of 55.66 ha, which occurred around the fott of Mount Singgalang, Tandikat, and Marapi. For the middle area of the Batang Anai watershed, the land-use changes that occurred were primary forest into ricefields cobering an area of 65.62 ha around the river. While in the downstream area of the Batang Anai watershed, the land-use change was from shrubs to shrimp ponds covering an area of 227.59 ha, which occurd on the palins and along the coast.